Introduction: Solidarities in Motion: Hybridity and Change in Migrant Support Practices. (March 2021) - della Porta, Donatella; Steinhilper, Elias
The so-called 'Eurozone' and 'migration' crises mark critical moments in Europe's recent political history and share similarities to the extent that they both have increased political conflict, mobilised large parts of civil society, and put renewed attention upon the notion of 'solidarity'. Focusing on the specific case of solidarity with migrants, this articles argues that times of crises have increasingly blurred the lines between contentious and non-contentious forms of civil society engagement. Scrutinising these dynamics of hybridisation, we bridge diverse, yet largely disconnected literatures, including social movement, civil society and humanitarian studies. In particular, we suggest that the disciplinary and analytical distinction between volunteering and non-profit activities on the one hand and social movements and political activism on the other is too rigid and does obscure parts of a complex phenomenon, which is characterised by activities that often intersect between humanitarian practices and contentious politics.